2020
DOI: 10.3390/jcm9061891
|View full text |Cite
|
Sign up to set email alerts
|

Available Technologies, Applications and Benefits of Teleorthodontics. A Literature Review and Possible Applications during the COVID-19 Pandemic

Abstract: Background: COVID-2019 spread rapidly throughout the world from China. This infection is highly contagiousness, has a high morbidity, and is capable of evolving into a potentially lethal form of interstitial pneumonia. Numerous countries shut-down various activities that were considered “not essential.” Dental treatment was in this category and, at the time of writing, only non-deferrable emergencies are still allowed in many countries. Therefore, follow-up visits of ongoing active therapies (e.g., orthodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 36 publications
1
85
0
Order By: Relevance
“…During emergencies, patient management could be affected, and new strategies aimed at providing oral health are required. In such conditions, instant messaging platforms could be efficiently used in order to perform healthcare consultancies and to manage patients remotely [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During emergencies, patient management could be affected, and new strategies aimed at providing oral health are required. In such conditions, instant messaging platforms could be efficiently used in order to perform healthcare consultancies and to manage patients remotely [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns regarding the appearance, epidemiology, risks and precautions during the disease crisis (Turkistani, 2020) and implications of coronavirus infection for orthodontic treatment (Sunjay Suri et al, 2020). Preventive strategies for infection control (Guo et al, 2020) and aerosol reduction (Maspero et al, 2020) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was the recommendation to use virtual assistance (Eliades & Koletsi, 2020;Maspero et al, 2020;Saccomanno et al, 2020) and assessments regarding the impact of the pandemic on orthodontic consultations and on the anxiety generated in patients and professionals (Martina et al, 2020;Peloso et al, 2020;Cotrin et al, 2020;Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, studies from multiple groups around the globe have reported on critical infection control measures [ 5 , 6 , 7 ] and guidelines for modifications to dental clinic workflows that were implemented during the pandemic [ 8 , 9 ]. Reports have also described the impact of COVID-19 on the practice of dental specialties, including oral medicine [ 10 ] oral and maxillofacial surgery [ 11 , 12 , 13 ], orthodontics [ 14 ] and endodontics [ 4 , 15 ].…”
Section: Introductionmentioning
confidence: 99%